O processo de criação de Escola Família Agrícola no município de Jaíba - MG - Luciano Vieira Lima (2018)
The main objective of this study was to analyze the processes inherent to the implementation of the Agricultural Family School (EFA) in the municipality of Jaíba, in the northern region of the State of Minas Gerais. By the proposal, the school will be guided by the Pedagogy of Alternation, that is, the students will spend a certain period in the school, in an integral regime, and another period in their domicile, with the familyand community of origin, integrating and socializing acquired knowledge. The proposal to implement the EFA encompasses a reality that is not very well discussed in conventional public schools: that of the student living in rural areas and who wants to stay in the rural environment, that is, there is also the scope of attendance to the target public with specific characteristics and by the need to redefine rural youth. For thatpurpose, a case study was used, since the researcher had reference to the remarkable presence of the Irrigation District of Jaíba, an irrigation project that raises the name of the municipality. The data collected during the research are predominantly descriptive with a qualitative approach. The interpretation of the collected data made it possible to infer that the proposal represents a challenge to the pedagogical practices instituted, a situation in which conditions are pointed to the effective implementation of the "educational space" and to the evaluation of the aspects of collective mobilization at the local level in view of the conceptualization of social capital under sociological view. According to the participant observer, it is suggested that the constitution of the Agricultural Family School depends on effective articulation between the social subjects involved, that is, the participation of public service, associations, entities, public or private institutions and civil society. Therefore, when the communities of Jaíba are involved in their promising activities, it is believed that the social force, rooted in local contexts and linked to the interests of rural people, can be a great propeller of development and an indispensable ally in the revitalization process the rural space and the visibility of rural youth.